KEBERADAAN MUSEUM KANDIL KEMILAU EMAS BAGI MASYARAKAT KAMPAR - Perdana, Rian; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The Golden Sheen Museum of Kandil is a museum in the form of traditional house of Koto Kampar that is Lontiok House which has 3 symbols of life that is upper part as area for creator, middle part as human area, and for lower part as natural area of evil. This is the reason why Kampar people choose to use the under-sections or under their houses as a place to store everyday supplies, and also keep the heirlooms at the top of their custom homes. This Gold Sheen Museum was built by the late Haji Hamid in about 1900. It was inaugurated on May 22, 1988 at Belimbing Island Kuok. Privileges of the museum Golden Glowing Candle is in addition to the bengunannya Traditional House also stored antiques that have historical value.Keywords: History, Museum, Golden Gazette Museum, Community.